ANALISIS KAUSALITAS ANTARA INVESTASI ASING LANGSUNG DAN EKSPOR DENGAN PERTUMBUHAN EKONOMI: STUDI KASUS MALAYSIA, THAILAND DAN INDONESIA - Andriga; Iin Indraswari (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2019)
The purpose of this study is to analyze the causal relationship between foreign direct investment and exports to economic growth in the countries of Malaysia , Thailand and Indonesia This research is used data from worldbank.org from 1987-2016. Research data were estimate by unit root test and Granger causality using E-views program 6.The results of this research by Granger causality test , it is found that there were no causal relationship between foreign direct investment and exports to economic growth in all three countries , because of the probability values generated exceeds a critical value of 5 per cent or 0,05.